Impact of the monetary policy instruments on Islamic stock market index return - Mohamed Shikh Albaity (Kiel Institute for the World Economy (IfW), 2011)
Previous studies found that Islamic stock market index in Malaysia (KLSI), does not react, or react negatively to interest rate, although one of the main criteria of Islamic finance is to avoid business and activities that yield interest because of its prohibition in Islamic laws. On the other hand, studies of Islamic stock market index in the US (DJIMI) found that there is no impact of interest rate on DJIMI. These two stock market indices have different screening criteria and different composite of securities. This study aims at investigating the monetary policy variables impact, the effect of interest rate, and the use of stock market indices as a hedge against inflation. It also examines the volatilities of monetary variables, interest rates, and inflation rate on two Islamic stock market indices. Using time series analysis such as GARCH the results are as follows. It is found that in the variance univariate models of the conventional indices that M1, M3, inflation rate, and real growth in GDP are significant in influencing KLCI volatility, while M2, M3, inflation rate and interest rate affected DJINA volatility. On the other hand, in the Islamic indices, KLSI and DJIMI variance is influenced by M2, M3, and inflation rate. In addition, in the multivariate model, DJIMI is influenced by the interest rate and the inflation rate in the mean and variance equations. In contrast, KLSI is influenced commonly in the mean and variance equations by M3, and the inflation rate.
Keywords: E4; E6; F4; 330; Macroeconomic volatility; GARCH; Islamic index; Aktienindex; Islam; Makroökonomischer Einfluss; Geldpolitik; Zins; Schätzung; Vergleich; Malaysia; USA